La equidad de género como parte de la responsabilidad social de las empresas - Pita Dueñas, Bárbara (2023)
Our society in the search for a better world has made great strides towards recognition, respect for human dignity and the comprehensive development of people and has found an ally in companies to achieve this goal. Companies constitute a strong instrument for the economic and social development of countries, as well as for the promotion of gender equity, and this is known as social responsibility, which is the subject that we will address in this paper.